2017
DOI: 10.1021/acs.jchemed.7b00070
|View full text |Cite
|
Sign up to set email alerts
|

Where Science Intersects Pop Culture: An Informal Science Education Outreach Program

Abstract: Attracting a general audience to STEM topics can be a challenge, and developing engaging and interactive instruction is important for educators in all fields. While many chemical educators have successfully used pop-culture themes to introduce their students to scientific concepts, these encounters are largely limited to formal classroom environments. Inspired by the successes of community science programs such as Science Café and Nerd Nite, science educators from two Nebraska campuses sought to broaden the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…The last question I asked is when women do watch science video, why do they watch them. Descriptively, there do seem to be differences between men and women in why they access videos that are consistent with the instrumental vs. curiosity-satisfying motivations described by Burks et al (2017). In this study, women primarily said that they watched the science videos for informational purposes (74%) with only 19% citing entertainment.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The last question I asked is when women do watch science video, why do they watch them. Descriptively, there do seem to be differences between men and women in why they access videos that are consistent with the instrumental vs. curiosity-satisfying motivations described by Burks et al (2017). In this study, women primarily said that they watched the science videos for informational purposes (74%) with only 19% citing entertainment.…”
Section: Discussionsupporting
confidence: 52%
“…Fewer studies, however, investigate adult women's engagement with informal STEM learning experiences. One such study by Burks et al (2017) examined gender-based engagement with their SciPop Talks! Program among college-aged adults.…”
Section: Gender Disparities Exist In Informal Science Learning Broadlymentioning
confidence: 99%
“…Moreover, while many educators have successfully used pop-culture themes to introduce their students to scientific concepts, educators have continually tried to use new techniques to engage their students such as the creation of a Science Caféon the pop-culture theme. 99 Video games 100 have become an increasingly important part of the entertainment industry, and they are also considered a form of art; 101 surprisingly, the use of video games to illustrate chemistry or chemical engineering 102 is relatively unexplored in the literature even though pedagogical video games exist. 103−105 Video games being used directly in education are an increasingly popular research topic, and even just playing commercial video games has been shown to benefit important skills in adult learners like effective communication, executive function, and resourcefulness.…”
Section: ■ Introductionmentioning
confidence: 99%
“…to unveil the name of a super hero (Clark Kent from Superman) or famous gimmicks of a character 88,98 such as "Bazinga" from the TV series The Big Bang Theory. Moreover, while many educators have successfully used pop-culture themes to introduce their students to scientific concepts, educators have continually tried to use new techniques to engage their students, such as the creation of a Science Café on the pop-culture theme 99 . Video games 100 have become an increasingly important part of the entertainment industry, and they are also considered a form of art 101 ; surprisingly the use of videogames to illustrate chemistry or chemical engineering 102 is relatively unexplored in the literature even though pedagogical videogames exist [103][104][105] .…”
mentioning
confidence: 99%
“…Adapting scientific principles in motion pictures is a well-known plot device, , and playing scenes from films that depict specific chemical concepts has been suggested as an entertaining addition to classroom topics to further engage students. The focus has generally been on more recent science fiction films, including popular franchises such as Star Wars , Harry Potter , and the Marvel universe since these are very familiar to contemporary students. While older movies have not been entirely ignored, films from the classic movie period (1930s–1960s) are more likely to be overlooked since students may view them as outdated, slower paced, and lacking the spectacular special effects and popular actors of the day.…”
Section: Introductionmentioning
confidence: 99%